From Realism to the Silver Age : New Studies in Russian Artistic Culture - Blakesley, Rosalind P. (Rosalind Polly); Samu, Margaret (De Kalb, IL : Northern Illinois University Press, 2014)
This volume of thirteen essays presents rigorous new research by western and Russian scholars on Russian art of the nienteenth and early-twentieth centuries. Over More than three decades after the publication of Elizabeth Valkenier's pioneering monograph, Russian Realist Art, this impressive collection showcases the latest methodology and subjects of inquiry, expanding the parameters of what has become an area of enormous intellectual and popular appeal. Major artists including Ilia Repin, Valentin Serov, and Wassily Kandinsky are considered afresh, as are the Peredvizhnik and Mir iskusstva movements and the Abramtsevo community. The book also breaks new ground to embrace subjects such as Russian graphic satire and children's book illustration, as well as stimulating aspects of patronage and display. Collectively, the essays include a range of approaches, from close textual readings to institutional critique. They also develop major themes inspired by Valkenier's work, among them: the emergence and evolution of cultural institutions, the development of aesthetic discourse and artistic terminology, debates between the Academy of Arts and its challengers, art criticism and the Russian press, and the resonance of various forms of nationalism within the art world. These and other questions engage multiple disciplines--those of art history, Slavic Russian studies, and cultural history, among others--and promise to fuel a vibrant and ascendant field.
6. Painting History, Realistically: Murder at the Tretiakov -- 7. The Contemporary Reception of Ilia Repin's Solo Exhibition of 1891 -- 8. Pavel Tretiakov's Icons -- 9. Closing the Books on Peredvizhnichestvo: Mir Iskusstva's Long Farewell to Russian Realism -- 10. Serov, Bakst, and the Reinvention of Russia's Classical Heritage -- 11. Between East and West: The Search for National Identity in Russian Illustrated Children's Books, 1800-1917 -- 12. Kandinsky's Sketch for ""Composition II, "" 1909-1910: A Theosophical Reading -- 13. Things That Are Not: Marianne Werefkin and the Condition of Silence
JSTOR
Keywords: Art, Russian -- Russia -- History -- 19th century; Art, Russian -- Russia -- History -- 20th century; Realism in art -- History; Silver age (Russian arts); Art russe -- Russie -- Histoire -- 19e siècle.; Art russe -- Russie -- Histoire -- 20e siècle.; Réalisme (Art) -- Histoire; Silver age (Russian arts); Realism in art; Art, Russian; Russia; 1800-1999; Elizabeth Valkenier, Ilia Repin, Valentin Serov, Wassily Kandinsky, Peredvizhnik movement, Mir iskusstva movement, Abramtsevo community, Russian graphic satire; History